2007
DOI: 10.1002/dvdy.21255
|View full text |Cite
|
Sign up to set email alerts
|

Flipping the switch: How a sperm activates the egg at fertilization

Abstract: Sperm interaction with an egg in animals was first documented 160 years ago in sea urchins by Alphonse Derbè s (1847) when he noted the formation of an "envelope" following the sperm's "approach" to the egg. The "envelope" in sea urchins is an obvious phenotype of fertilization in this animal and over the past 35 years has served to indicate a presence of calcium released from cytoplasmic stores essential to activate the egg. The mechanism of calcium release has been intensely studied because it is a universal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 153 publications
(128 reference statements)
0
83
0
Order By: Relevance
“…Cite this article as Cold Spring Harb Perspect Biol 2011;3:a006767 excellent recent reviews have addressed this topic in depth Parrington et al 2007;Horner and Wolfner 2008b) and therefore only the most salient and outstanding aspects of PLCz will be discussed here. As noted earlier, research in a variety of species including mammals showed that fertilization-associated [Ca 2þ ] i responses require the same agonists and signaling cascades that cause Ca 2þ release in somatic cells (Miyazaki et al 1993;Miyazaki and Ito 2006).…”
Section: Signaling During Mammalian Fertilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cite this article as Cold Spring Harb Perspect Biol 2011;3:a006767 excellent recent reviews have addressed this topic in depth Parrington et al 2007;Horner and Wolfner 2008b) and therefore only the most salient and outstanding aspects of PLCz will be discussed here. As noted earlier, research in a variety of species including mammals showed that fertilization-associated [Ca 2þ ] i responses require the same agonists and signaling cascades that cause Ca 2þ release in somatic cells (Miyazaki et al 1993;Miyazaki and Ito 2006).…”
Section: Signaling During Mammalian Fertilizationmentioning
confidence: 99%
“…Generally speaking, species can be categorized either as displaying a single [Ca 2þ ] i increase, which is the case of sea urchins, starfish, frogs, and fish, or showing multiple [Ca 2þ ] i changes, also known as oscillations, which is the case of nemertian worms, ascidians, and mammals (Stricker 1999;Miyazaki and Ito 2006). Elucidation of the signaling cascades and identification of the molecules/receptor(s) that initiate the Ca 2þ signal at fertilization has proven elusive, and this review will not dwell on that literature; readers are referred to excellent recent reviews on the subject (Whitaker 2006;Parrington et al 2007). Nonetheless, research has found that Src-family kinases (SFKs) and phospholipase Cg (PLCg) are involved in the activation of the phosphoinositide pathway and production of inositol 1,4,5-trisphosphate (IP 3 ) during fertilization in sea urchins, starfish, and frogs, which reflects the contribution of a plasma membrane receptor/signaling complex (Giusti et al 1999;Sato et al 2000).…”
mentioning
confidence: 99%
“…This elevated Ca 2ϩ originates either from the external environment, from internal cellular stores, or from some combination of the two. The source of fertilization-induced Ca 2ϩ waves has been the subject of several excellent recent reviews (Swann et al, 2006;Townley et al, 2006;Parrington et al, 2007), so we only give a brief overview here.…”
Section: Triggers Of Egg Activation Spermmentioning
confidence: 99%
“…Studies show that the initiation of the fertilization calcium wave in verterbrates can generally be best explained by a diffusion of a GENERAL INTRODUCTION 24 sperm-specific activating substance released into the oocyte after gamete fusion (Swann et al, 2006;Parrington et al, 2007;Saunders et al, 2007;Whitaker, 2006). This sperm factor corresponds to a spermspecific phospholipase C (PLC) called PLCζ (Swann and Lai, 2013;Ito et al, 2011) (Fig 6).…”
Section: Fertilizationmentioning
confidence: 99%
“…After fertilization, the egg is activated and initiates its developmental program, and the haploid nuclei of the two gametes fuse to form the genome of a new diploid organism. A centrally important factor in initiating egg activation at fertilization is a rise in free Ca 2+ in echinoderms, ascidians, and vertebrate eggs (reviewed by Runft et al, 2002).Studies show that the initiation of the fertilization calcium wave in verterbrates can generally be best explained by a diffusion of a GENERAL INTRODUCTION 24 sperm-specific activating substance released into the oocyte after gamete fusion (Swann et al, 2006;Parrington et al, 2007;Saunders et al, 2007;Whitaker, 2006). This sperm factor corresponds to a spermspecific phospholipase C (PLC) called PLCζ (Swann and Lai, 2013;Ito et al, 2011) (Fig 6).…”
mentioning
confidence: 99%